2015
DOI: 10.1007/s00281-015-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic value of TRPV1 and TRPA1 in diabetes mellitus and obesity

Abstract: Diabetes mellitus and obesity, which is a major risk factor in the development of type 2 diabetes mellitus, have reached epidemic proportions worldwide including the United States. The current statistics and forecasts, both short- and long-term, are alarming and predict severe problems in the near future. Therefore, there is a race for developing new compounds, discovering new receptors or finding alternative solutions to prevent and/or treat the symptoms and complications related to obesity and diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 85 publications
1
57
0
2
Order By: Relevance
“…The studies determined that liver-related neurons receive transient receptor potential vanilloid type 1 (TRPV1) containing inputs. TRPV1 is a non-selective cation channel and has been linked to the development and progression of type 1 diabetes mellitus and T2D (134), and recent reviews have discussed its role in diabetes mellitus and obesity in further detail (135, 136). The TRPV1-dependent excitation of liver-related PVN neurons was diminished in a hyperglycemic, insulin-deficient mouse model.…”
Section: Liver-related Neurons In the Hypothalamusmentioning
confidence: 99%
“…The studies determined that liver-related neurons receive transient receptor potential vanilloid type 1 (TRPV1) containing inputs. TRPV1 is a non-selective cation channel and has been linked to the development and progression of type 1 diabetes mellitus and T2D (134), and recent reviews have discussed its role in diabetes mellitus and obesity in further detail (135, 136). The TRPV1-dependent excitation of liver-related PVN neurons was diminished in a hyperglycemic, insulin-deficient mouse model.…”
Section: Liver-related Neurons In the Hypothalamusmentioning
confidence: 99%
“…The role of TRPV1 in these settings, particularly in endothelial dysfunction in obesity and diabetes, has recently been demonstrated (Lee et al . ) and reviewed (Derbenev & Zsombok ). Nevertheless, TRPV1‐dependent renovascular changes in these pathophysiological conditions need further investigations.…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 99%
“…Accumulating evidence indicates that TRPV1 plays an essential role in the underlying processes of heart failure, indicating that the modulation of TRPV1 may be a potential target for CHF treatment in diabetes [2,28]. Indeed, defects of TRPV1 have been associated with the occurrence of heart failure in type 1 and 2 diabetes mellitus due to their effects on ROS production, Ca 2+ transients, eNOS activity, adiponectin and leptin signaling control, the modulation of neuronal activity, microcirculatory vasodilation, and the regulation of myocardial blood flow [12,[29][30][31][32].…”
Section: Cellular Physiologymentioning
confidence: 99%
“…Recently, Issa reported that increased expression of transient receptor potential vanilloid 1 (TRPV1) protein is observed in rats with angiotensin II (Ang II)-dependent malignant hypertension, which indicates that TRPV1 may be an important contributing factor to these effects of Ang II [11]. Moreover, the role of the TRPV1 channel in the regulation of cardiovascular dysfunction in diabetes has been established [2]. Zheng demonstrated impaired TRPV1 activity and deficient levels of primary downstream transmitters, such as calcitonin gene related peptide (CGRP) and substance P (SP), in the hearts of diabetic mice and patients [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation